High ZnPP-forming food-grade lactic acid bacteria as a potential substitute for nitrite/nitrate to improve the color of meat products. (June 2021) - Kauser-Ul-Alam, Md.; Hayakawa, Toru; Kumura, Haruto; Wakamatsu, Jun-ichi
Abstract: Zinc protoporphyrin IX (ZnPP)-forming food-grade lactic acid bacteria (LAB) were screened from various sources for their ability to improve the color of meat products. The effects of salt and nitrite on the ZnPP-forming ability of these bacteria were also investigated. Finally, these bacteria were applied in salt-added minced meat to assess their ability to improve the color. Twenty-five LAB were screened for their ZnPP-forming ability in pork. Most of the strains exhibited maximum growth anaerobically in 3% salt at 30 °C and grew well at pH 5.5 and 6.5. Moreover, 3% salt slightly retarded ZnPP formation; however, nitrite completely inhibited ZnPP formation in all the ZnPP-forming LAB. Thirteen LAB (avoiding duplication and non-food-grade) could form ZnPP in salt-added minced meat, resulting in improvement of the bright red color, high ZnPP autofluorescence, and increased fluorescence intensity. Finally, considering the safety, Lactobacillus plantarum, Lactococcus lactis subsp. cremoris, and Leuconostoc lactis were suggested as promising candidates to improve the color of meat products. Highlights: Twenty-five isolates were defined as high ZnPP-forming lactic acid bacteria. All ZnPP-forming strains exhibited maximum growth in 3% salt. Salt slightly affected ZnPP-formation even in ZnPP-forming strains. No formation of ZnPP by the strains was observed in the presence of nitrite. Edible lactic acid bacteria improved the color of salt-added minced meat.